Economic Globalization and New Imperialism: Resistance in Robert Newman’s The Fountain at the Center of the World - Dagamseh, Abdullah; Boukemache, Wissame (The international journal of literary humanities, 2019)
This article reads Robert Newman’s novel, “The Fountain at the Center of the World,” in light of globalization as an analytical and explanatory tool to challenge the postmodern view of globalization that short-circuits the field of literary and cultural studies. This reading offers us a better understanding of globalization as a long historical process that can be explored across various dimensions politically, economically, socially, and culturally. Moreover, unlike Michael Hardt and Antonio Negri’s argument in “Empire,” where they declare the demise of state-oriented imperialism as the primary agent of global capitalism, we claim that the state still plays a major role in orchestrating the processes of capital accumulation in the contemporary era of globalization. Finally, exposing the oppressive forces that capitalist imperialism propagates, the novel conjures up acts of resistance that go beyond the violent/non-violent, personal/public, and national/international essentialist categorizations.